1994
DOI: 10.1093/infdis/170.5.1316
|View full text |Cite
|
Sign up to set email alerts
|

Carriage Of Group B Streptococci In Pregnant Gambian Mothers And Their Infants

Abstract: The prevalence of group B streptococcal (GBS) colonization was studied in 136 pregnant women and their newborn infants by collecting vaginal and rectal swabs from the mothers and throat, rectal, and umbilical swabs from their infants. Maternal and infant colonization rates were 22% and 23%, respectively. One-third of infants born to colonized mothers and 15% of infants born to noncolonized mothers had GBS isolated. Of GBS-colonized infants, 50% remained colonized at the mean age of 2 months. Type V was the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
40
4
1

Year Published

1995
1995
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 9 publications
15
40
4
1
Order By: Relevance
“…For example, GBS colonization is prevalent in the United States (15-25%), 6 Jordan (30%), 17 Trinidad (31%), 18 and Gambia (22%). 19 The prevalence rate of 6.0% in our pregnant population compares with the 4% seen by DeLourdes Collado and others in Mexico City. 8 Low prevalence rates have also been reported in Italy (6.6%), 20 Turkey (8.7%), 21 and Ethiopia (9%).…”
Section: Discussionsupporting
confidence: 68%
“…For example, GBS colonization is prevalent in the United States (15-25%), 6 Jordan (30%), 17 Trinidad (31%), 18 and Gambia (22%). 19 The prevalence rate of 6.0% in our pregnant population compares with the 4% seen by DeLourdes Collado and others in Mexico City. 8 Low prevalence rates have also been reported in Italy (6.6%), 20 Turkey (8.7%), 21 and Ethiopia (9%).…”
Section: Discussionsupporting
confidence: 68%
“…Some streptococci were found to belong to group B, an organism which can be highly pathogenic for newborns, particularly at the time of delivery, when it is associated with neonatal sepsis and premature delivery [19]. The prevalence of streptococcus B seems in this study to be particularly low (1-3%) compared to that reported in other parts of Africa [20], where surprisingly the high prevalence of streptococcus was not associated with disease in newborns.…”
Section: Discussioncontrasting
confidence: 61%
“…However, there is an urgent need to establish the disease burden arising from this colonization as all studies reported so far failed to address this. However, in studies carried out in other African countries, higher prevalence rates were obtained, such as: Malawi (16.5%) (12), Gambia (22.0%) (13), Zimbabwe (20-32%), (14) and) Ivory Coast (19.0%) (23).…”
Section: Discussionmentioning
confidence: 97%
“…Most data on GBS epidemiology are from Europe and North America and a few cases of GBS infections (5-7) and carriage as a public health problem have been reported from Nigeria (5,8,9,10,11) and other African countries (12,13,14). This study was designed to determine the prevalence of GBS in pregnancy and the incidence of GBS infections in intrapartum in a tertiary hospital in Nigeria.…”
Section: Introductionmentioning
confidence: 99%